Proposal of the optional course Mouth Guards in Sports - Liuba Díaz Valdés; Lisbet Sánchez Rodríguez; Raúl Luis Valle Lizama (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The protection of the dentomaxillofacial structures during sports activities and physical exercise is increasingly necessary, so the Superior Technician in Stomatological Prosthesis must know how to make mouth guards, and develop knowledge on these topics. Objective: To design an optional course in the first year of the speciality Superior Technician in Stomatological Prosthesis that contributes to the training of a more qualified professional to make mouth guards. Methods: A qualitative descriptive study was carried out. Theoretical methods: (historical-logical, inductive-deductive, analytical-synthetic, systemic-structural and modeling), and empirical methods: (documentary review, specialist criteria) were used. Results: An optional face-to-face and structured in three topics course of 20 hours was designed. The optional course Mouth Guards in Sports contributes to promoting curricular activities which support the development of a culture on oral protection. Conclusions: The design of the optional course corresponds to the learning needs of the Superior Technician in Stomatological Prosthesis to make mouth guards.